Integrating Chinese ink painting into visual communication education: fostering creativity, aesthetic sensibilities, and visual communication skills among students - Wang, Wenyu; Alli, Hassan; Saion, Indastri (UK Zhende Publishing Group, 2024)
This study delves into incorporation of Chinese ink drawing within visual communication education, evaluating its impact on student's creativity, aesthetic discernment, and visual communication proficiencies. Conducting a comprehensive literature review, we employed the PRISMA methodology to sift through pertinent articles. Analyzing 167 publications between 2019 and 2023 using the TCCM (Theory-Context-Method-Finding) framework reveled insights regarding Chinese ink painting's integration into art and design education. Results affirm that employing Chinese ink techniques nurtures creativity, facilitating original idea generation and aesthetic expression. Exposure to this art form also deepens students' grasp of aesthetic principles like balance and simplicity in their work. However, the focus on short-term outcomes prompts the necessity for longitudinal research to grasp the prolonged impacts. Understanding its influence on visual communication in the digital age remains crucial, highlighting the need for further investigation. In summary, this provides a concise yet comprehensive overview, discussing background, objectives, analytical methodology, parameters and key findings. While the integration of Chinese ink drawing exhibits promise in enhancing creativity and aesthetic sensibilities, comprehensive exploration and consideration of long-term impacts in the digital era are warranted. This study advocates for increased scholarly attention, foreseeing potential enhancements in visual communication education curricula.